2022
DOI: 10.1097/grf.0000000000000699
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy Outcomes Associated With Use of Tobacco and Marijuana

Abstract: Tobacco and marijuana are the most common drugs of abuse among pregnant women. Cigarettes have been extensively studied and increase the risk of miscarriage, preterm birth, premature rupture of membranes, placental dysfunction, low birth rate, stillbirth, and infant mortality. There are sparse data on the specific effects of electronic cigarettes and smokeless tobacco in pregnancy. Literature on marijuana in pregnancy is limited by confounding, bias, and the retrospective nature of studies that do not capture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…The findings for the latter two studies need to be treated with caution as they simultaneously reported no significant difference in risk for exclusive-vaping and non-use. This implies that smoking does not pose an elevated risk, when it has been well established that smoking poses an increased risk [ 1 ], and therefore raises questions about the validity of their findings for vaping. One study observed that vapers (combining exclusive-vapers and dual-users) had a greater risk of depression symptoms during pregnancy than non-users or exclusive-smokers [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The findings for the latter two studies need to be treated with caution as they simultaneously reported no significant difference in risk for exclusive-vaping and non-use. This implies that smoking does not pose an elevated risk, when it has been well established that smoking poses an increased risk [ 1 ], and therefore raises questions about the validity of their findings for vaping. One study observed that vapers (combining exclusive-vapers and dual-users) had a greater risk of depression symptoms during pregnancy than non-users or exclusive-smokers [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…We excluded studies without full texts (e.g., abstract only). Although we sought all health outcomes, we anticipated including most of the important clinical outcomes for pregnant women, fetuses and infants identified in reviews of the health consequences of NTR and smoking [ 1 , 4 , 21 ], including miscarriage, stillbirth, preterm birth, birthweight, low birthweight, small for gestational age, admission to neonatal intensive care, caesarean section, congenital abnormalities and neonatal death. We also anticipated that biomarker studies would include most of the biomarkers of toxicants and carcinogens that have been assessed in studies of vaping among non-pregnant populations [ 12 ], including nitrosamines, VOCs, PAHs and heavy metals.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…While retrospective observational studies suggest that outcomes like preterm birth and small for gestational age (SGA, defined as birthweight less than 10 th percentile by gestational age) are associated with prenatal cannabis use, these are also well-characterized as a sequelae of prenatal tobacco use. [12][13][14] We sought to prospectively evaluate the impact of PCU on outcomes in birthing persons with pre-pregnancy cannabis use and negative self-report of nicotine use, who either continued cannabis in pregnancy or did not. We examined whether PCU, as well as intensity of use, was associated with adverse outcomes for the pregnant person or neonate.…”
Section: Introductionmentioning
confidence: 99%
“…For example, among pregnant individuals, cannabis and tobacco co-use is up to three times more common than cannabisonly use (Coleman-Cowger et al, 2017;Ko et al, 2018), a majority of pregnant individuals who smoke cigarettes also report use of cannabis (Ko et al, 2015), and women who report co-use in pregnancy are more likely to continue using both or either substance during pregnancy or postpartum (Coleman-Cowger et al, 2017;De Genna et al, 2018;England et al, 2020;Ko et al, 2020;Qato et al, 2020). Use of tobacco or cannabis across the perinatal period is associated with numerous negative birth outcomes, such as low birth weight, premature birth, respiratory illness, cognitive deficits, and increased secondhand smoke exposure (Centers for Disease Control and Prevention, 2001;Duko et al, 2023;Lin et al, 2023;Regan et al, 2021), with co-use associated with worse neurobehavioral and birth outcomes (Coleman-Cowger et al, 2018;De Genna et al, 2019;Layoun et al, 2022;Stroud et al, 2018Stroud et al, , 2020.…”
mentioning
confidence: 99%